RANCANG BANGUN ALAT UJI TARIK SERAT ALAM UNTUK MENDUKUNG INDUSTRI NASIONAL - Abubakar Dabet Dabet (Jurnal Ilmiah Teknik Mesin POROS, 2018)
Currently the development trend of composite materials shifts to the reuse of natural fiber (back to nature) as a substitute for synthetic fibers. Measurement of the mechanical properties of fiber (reinforcement) plays an important role in quality control. One of the most important mechanical properties of fiber is its tensile strength. Tensile strength of fiber can be known through tensile test (tensile test). To do tensile test (tensile test) fiber required tensile test machine (tensile test machine). The tensile test equipment used today is a foreign-made commercial tensile test device imported at an exorbitant price. These conditions cause obstacles in the development of basic industries and natural fiber technology. Most laboratories in higher education institutions and other technology research institutions do not have tensile test equipment support. The purpose of this research is to design a natural fiber tensile test apparats which is cheap and easy to operate. The research method using design tool design (design and manufacture). The result of this research is prototype of natural fiber tensile test which has been successfully tested with technical data: 5N loading capacity, calibration curve accuracy: N = 1.052 V and loading rate 0.014 N/s. The result of tensile test to one natural fiber that used abaca fiber obtained the value of tensile strength of an average of 579,90 MPa. The result of tensile test obtained is comparable with the data of tensile test results in existing literatures then there is conformity with the value of tensile strenght. The results of this study are expected to provide benefits for researchers, academics and industry in supporting the development of national natural fiber industry to increase the competitiveness of industries at the international level.